Sistem Kendali Kecepatan Motor Arus Searah tanpa Sensor Kecepatan dengan Observer Metode R - Harini, Bernadeta Wuri; Muda, Vincentius Hosea Pniel; Afrizal, Stefanus Derryan Vicky; Irwandi, Marcellius (Politeknik Sukabumi, 2025)
Most industries control the motor speed to get the speed as desired speed. One method of controlling motor speed is a speed sensorless control system. In this study, a speed sensorless control system is designed to control the speed of a DC motor. In this system, the motor speed is not measured directly using a speed sensor installed on the rotor, but it’s calculated by an observer from the values of stator current and voltage that are measured using current and voltage sensors. In this study, the R method observer was used. The estimated speed will be compared with the reference speed. The On-off controller will process these speed differences to adjust the motor to have the same speed as the desired speed. In this study, a DC motor speed sensorless control system with an R method observer that has a performance lower than the L-R method will be investigated to determine whether it can control a DC motor well. The control system consists of an EG-530AD-2F CW DC motor, INA 219 current and voltage sensors, an L298N type DC motor drive, and an Arduino Uno microcontroller as the overall system processing tool. This study can prove that the R method observer with the addition of an On-off mode controller can control the motor speed with good performance. The system response has steady-state error characteristics of 0.59%, a maximum overshoot of 0.49%, a rise time of 1.3 seconds, and a settling time of 1.9 seconds.